A surface micro-arc oxidation treatment process for corrosion-resistant motor aluminum castings

CN123005477APending Publication Date: 2026-10-30YANGZHOU ZHONGQING ELECTROMECHANICAL EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611126461.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种耐腐蚀电机铝铸件表面微弧氧化处理工艺,解决了现有电机铝铸件往往由于表面存在高硅相,导致微弧氧化处理过程中电场分布及导电性存在微区差异,这往往会引发放电不均匀以及局部能量集中,最终使得氧化膜层孔隙率偏高、致密度欠佳,难以满足电机外壳对高防腐性能的问题

Benefits of technology

[0040]1、本发明通过在电解液中引入聚天冬氨酸作为吸附屏蔽剂,并配合高频低温阶段的参数控制,使吸附屏蔽剂优先附着于铝铸件表面的硅相富集区形成物理绝缘层;提高了局部微区的界面阻抗,引导放电电流向未被屏蔽的铝基体区域分布,改善了高硅相分布不均引起的局部放电集中现象,有助于获得厚度与结构相对均匀的初始氧化膜层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123005477A_ABST
    Figure CN123005477A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of metal surface treatment, and discloses a surface micro-arc oxidation treatment process for corrosion-resistant motor aluminum castings, which comprises pretreatment, micro-arc oxidation treatment and post-treatment; the micro-arc oxidation treatment adopts a variable impedance composite electrolyte containing a film-forming base salt, a pH regulator, an adsorption shielding agent and a high-temperature sealing agent, and the treatment process sequentially comprises a high-frequency low-temperature induction shielding period treatment and a low-frequency warming in-situ melting sealing period treatment; in the early stage, constant low temperature is controlled, and a high-frequency pulse current is applied, so that the shielding agent forms an insulating layer in the silicon-rich area, the current is guided to the matrix to improve uneven discharge; in the later stage, the bath is controlled to be warmed, the pulse frequency is simultaneously reduced, and the current density is increased, so that the high-temperature sealing agent is driven into the discharge micropores to be in-situ melted and deposited. The process improves the concentrated discharge phenomenon of the high-silicon aluminum castings, realizes in-situ self-sealing of the micropores, reduces the porosity of the film layer, and improves the corrosion resistance of the motor aluminum castings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal surface treatment technology, specifically a micro-arc oxidation process for the surface of corrosion-resistant aluminum castings for motors. Background Technology

[0002] With the development of lightweight technology, aluminum alloy castings are widely used in the manufacture of housings for new energy motors and industrial motors. To ensure the casting fluidity and mechanical properties of the material, aluminum castings for motors typically use aluminum alloys with high silicon content, such as A356 or ADC12. Since motors often face complex operating conditions such as humidity and salt spray during actual service, high requirements are placed on the corrosion resistance of their housings. Micro-arc oxidation technology, as a surface treatment process that can grow a ceramic oxide film in situ on the aluminum alloy surface, is widely used to improve the corrosion resistance of aluminum parts.

[0003] Conventional micro-arc oxidation processes can achieve relatively ideal film layers when processing low-alloy aluminum materials, but they face engineering adaptability issues when processing aluminum castings for motors containing high silicon phases. These castings contain a large number of discontinuous silicon phases. Due to the inherent physical differences in conductivity and surface condition between the silicon phase and the surrounding aluminum matrix, the micro-electric field distribution on the casting surface is easily distorted when high voltage is applied for micro-arc oxidation. This uneven conductivity in the micro-areas causes the micro-arc discharge behavior to deviate from the conventional state, making the discharge current tend to accumulate in highly conductive silicon-rich areas or at phase boundary defects, triggering localized intense discharges and energy concentration.

[0004] Due to the concentrated effects of partial discharge, the growth process of the micro-arc oxide film is difficult to maintain uniformity. When the molten oxide cools and solidifies, microscopic thermal stress cracks are generated around the silicon phase interface. Simultaneously, traditional electrolyte formulations and fixed electrical parameter settings are insufficient to actively shield or intervene in these differences in substrate conductivity. This results in the discharge micropores left during film formation being difficult to be effectively filled by the reactants themselves. These unsealed micropores and unevenly distributed phase boundary cracks constitute penetration channels through the film, allowing corrosive media to easily penetrate the internal metal substrate along these channels. Consequently, the final oxide film exhibits poor density and substandard corrosion resistance, failing to meet the design requirements of modern motor housings for long-term service under harsh conditions. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a micro-arc oxidation process for the surface of corrosion-resistant aluminum castings for motors. This process solves the problem that existing aluminum castings for motors often have high silicon phases on their surface, leading to micro-regional differences in electric field distribution and conductivity during the micro-arc oxidation process. This often results in uneven discharge and local energy concentration, ultimately causing the oxide film layer to have high porosity and poor density, making it difficult to meet the high corrosion resistance requirements of motor housings.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] This invention provides a micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors, employing the following technical solution:

[0008] A micro-arc oxidation process for the surface of corrosion-resistant aluminum castings for motors includes the following steps:

[0009] Pre-treatment is performed on the aluminum castings of the motor to be processed;

[0010] The pre-treated aluminum casting of the motor is placed as the anode in a variable impedance composite electrolyte and connected to a pulse power supply for micro-arc oxidation treatment. Then, high-frequency low-temperature induced shielding period treatment and low-frequency heating in-situ melting and sealing period treatment are performed sequentially.

[0011] In the high-frequency low-temperature induced shielding period treatment, the bath solution is kept at a constant low temperature while a high-frequency pulse current is applied;

[0012] In the low-frequency heating in-situ melting and sealing process, the bath liquid is heated in a controlled manner, while the pulse frequency is reduced and the current density is increased.

[0013] The variable impedance composite electrolyte is composed of a reference solvent, a film-forming base salt, a pH adjuster, an adsorption shielding agent, and a high-temperature sealing agent.

[0014] Based on the standard solvent volume, the added concentrations are: 8.0 g / L to 15.0 g / L of film-forming base salt, 2.0 g / L to 5.0 g / L of pH adjuster, 2.0 g / L to 5.0 g / L of adsorption shielding agent (converted to absolute solids content), and 3.0 g / L to 8.0 g / L of high-temperature sealing agent;

[0015] Corrosion-resistant aluminum castings for motors can be obtained by post-processing the micro-arc oxidation treated aluminum castings.

[0016] By adopting the above technical solution, this process uses a variable impedance composite electrolyte containing an adsorption shielding agent and a high-temperature sealing agent, combined with a two-stage variable frequency and temperature electrical control program. This can significantly improve the local defects caused by uneven silicon phase distribution on the surface of aluminum castings, thereby obtaining an oxide film layer with uniform film formation, low porosity, and good corrosion resistance. Its reaction process and principle mainly include the following aspects:

[0017] High-frequency low-temperature induced shielding treatment mechanism. The electrolyte is maintained at a low temperature of 10℃ to 15℃. The high activity of the polycarboxyl functional groups in the molecular structure of the adsorption shielding agent at low temperature is utilized to promote its preferential adsorption on the eutectic silicon enrichment area and high conductivity micro-region on the surface of the aluminum casting, forming a physical insulating adsorption layer.

[0018] This physically insulating adsorption layer increases the local interfacial impedance, forcing the discharge current to redistribute to the unshielded aluminum substrate region, reducing the probability of micro-arc discharge accumulating around the silicon phase. During this electrochemical stage, the aluminum anode substrate undergoes electrochemical dissolution, transforming into aluminum ions, which then migrate outwards and combine with hydroxide ions migrating towards the anode interface in the electrolyte to form a film, generating solid alumina. Simultaneously, the application of a high-frequency pulsed current disperses the discharge energy and miniaturizes the single-pulse energy, which facilitates dense and uniform nucleation growth of the initial oxide film on the aluminum substrate surface, thereby controlling the pore structure of the underlying film layer.

[0019] The mechanism of low-frequency heating in-situ melting sealing treatment. By increasing the bath temperature to 35℃ to 42℃, the thermal motion of the adsorbed shielding agent intensifies and desorption occurs, exposing the surface micro-regions that were initially shielded. During this process, the total current density is simultaneously increased by a step and the bipolar pulse frequency is reduced, resulting in a significant increase in single-pulse discharge energy, and the micro-arc discharge transitions to the strong spark stage. At this point, the high-temperature sealing agent anions in the system enter the discharge micropore channels under the drive of the electric field, and a temperature of over 1500℃ is instantly generated inside the micropore channels.

[0020] Specifically, tungstate ions entering the microporous channels undergo in-situ sintering transformation with free aluminum ions under the high temperature generated by micro-discharge, producing a composite ceramic phase deposit containing aluminum, tungsten, and oxygen. The molten composite ceramic phase can fill the discharge micropores and shrinkage cracks generated during cooling and solidification, completing the in-situ self-sealing of the pores inside the oxide film layer, thereby blocking the penetration channels of corrosive media.

[0021] Preferably, the film-forming base salt is sodium silicate or potassium silicate; the pH adjuster is potassium hydroxide; the adsorption shielding agent is polyaspartic acid; the high-temperature sealing agent is sodium tungstate or potassium tungstate; and the reference solvent is deionized water with a conductivity between 10 μS / cm and 14 μS / cm at room temperature.

[0022] By adopting the above technical solutions, polyaspartic acid has excellent complexing and adhesion properties in a strong alkaline system, and can provide a certain steric hindrance effect and insulation shielding effect at low temperature. Sodium tungstate or potassium tungstate has a low melting point and high oxide structural stability, and is easy to deposit and seal pores after melting in the micro-arc discharge channel. Deionized water as a reference solvent eliminates the electrochemical interference of impurity ions.

[0023] Preferably, the preparation process of the variable impedance composite electrolyte is as follows: the film-forming base salt and pH adjuster are added sequentially to the reference solvent and stirred until dissolved to prepare an alkaline solution with a pH value controlled between 12.5 and 12.9; the adsorption shielding agent is added to the alkaline solution and stirred to disperse; then the high-temperature sealing agent is added and stirred until the system presents a homogeneous state.

[0024] By adopting the above technical solutions and clarifying the feeding sequence and pH control standards, the aim is to prevent polyaspartic acid from agglomerating and failing when the local concentration is too high or the pH is mismatched, and to reduce the possibility of tungstate and silicate forming insoluble colloids in the early stage of dissolution, which is conducive to maintaining the component uniformity of the composite electrolyte during long-term treatment.

[0025] Preferably, the pretreatment specifically involves: immersing the aluminum casting of the motor in a neutral degreasing solution at a temperature of 45°C to 55°C, and applying ultrasonic-assisted cleaning at a frequency of 28kHz to 40kHz for 5 to 10 minutes; removing the degreased aluminum casting of the motor, and rinsing it twice in countercurrent pure water in deionized water with a conductivity of less than 15μS / cm, with each pure water rinse lasting for 2 to 3 minutes.

[0026] By adopting the above technical solution, the cutting fluid and grease are removed by using ultrasonic cavitation effect combined with neutral degreasing liquid. Compared with conventional methods, this can avoid excessive corrosion and roughening of the high-silicon aluminum alloy surface caused by strong alkali or strong acid pretreatment, and provide a substrate surface with uniform activity for subsequent adsorption shielding and film formation reaction.

[0027] Preferably, the pulse power supply is a bipolar pulse power supply; the operating parameters for the high-frequency low-temperature induced shielding treatment are set as follows: the bath temperature is maintained at 10℃ to 15℃; the bath flow field is maintained in a laminar flow state with a Reynolds number of less than 2000; and the total current density is set to 1.5A / dm³. 2 Up to 2.5A / dm 2 Set the anode duty cycle to 55% to 65%, the cathode duty cycle to 5% to 10%, and the bipolar pulse frequency to 1500Hz to 2000Hz; continue processing for 10 to 15 minutes under these operating parameters.

[0028] By adopting the above technical solution, the bath liquid is kept in a laminar flow state, which can reduce the scouring and peeling effect of fluid shear force on the polyaspartic acid physical adsorption layer, so as to ensure the integrity of the shielding layer; while setting a combination of low current, high duty cycle and high frequency parameters to provide continuous and low-energy spark discharge helps to suppress the generation of destructive large electric arcs.

[0029] Preferably, the operating parameters for the initial stage of the low-frequency heating in-situ melting and sealing process are adjusted as follows: cooling is stopped, and the bath solution is heated at a rate of 0.9℃ / min to 1.25℃ / min using Joule heating; when the bath solution temperature exceeds 25℃, the circulation pump is turned on to switch the bath solution flow field to a strongly turbulent state with a Reynolds number greater than 4000; simultaneously, the total current density is stepped up to 4.0 A / dm³. 2 Up to 6.0A / dm 2 The anode duty cycle will be lowered to 25% to 35%, and the cathode duty cycle will be increased to 25% to 35%.

[0030] By employing the above technical solution, Joule heating is used to uniformly raise the temperature of the system, and strong turbulence is combined to accelerate the detachment of discharge bubbles and the mass transfer of reactants within the micropores, preventing sintering damage to the bottom of the pores due to localized overheating. Furthermore, the cathode duty cycle is significantly increased, and cathode pulse discharge is used to eliminate the accumulation of positive charges on the oxide film surface, reducing concentration polarization and maintaining the high efficiency of subsequent forward pulse discharge.

[0031] Preferably, during the low-frequency heating in-situ melting and sealing process, as the bath liquid continues to heat up, the bipolar pulse frequency is continuously and in reverse adjusted downwards by the PLC system until the bath liquid temperature reaches the endpoint temperature of 35°C to 42°C. At this endpoint temperature, the bipolar pulse frequency drops to 200Hz to 400Hz.

[0032] By adopting the above technical solution, a control strategy with inverse linkage between temperature and frequency was established. As the temperature rises, the interfacial reactivity increases, and the pulse frequency is simultaneously reduced to increase the single-pulse conduction time, allowing the spark discharge energy to fully penetrate into the pores of the film layer, driving the high-temperature sealing agent to undergo a full melting and deposition reaction.

[0033] Preferably, the total processing time for the low-frequency heating in-situ melting and sealing treatment is 20 to 30 minutes.

[0034] By adopting the above technical solution, it is ensured that the surface of the aluminum casting completes the structural transformation and accumulates a sufficient film thickness, preventing incomplete sealing due to insufficient processing time, and also avoiding the risk of the film surface turning into a powdery and loose state due to excessive processing time.

[0035] Preferably, the post-treatment is as follows: after immersing the aluminum casting of the motor in deionized water at room temperature for 3 to 5 minutes, it is immersed in deionized water at a temperature of 80°C to 90°C for 10 to 15 minutes for hot water sealing treatment, and then taken out and dried.

[0036] By adopting the above technical solution, the amorphous alumina on the surface of the oxide layer absorbs water and undergoes a hydration reaction by utilizing the sealing effect of hot water, causing the volume to expand. This physically seals the micropores of the outermost layer, further improving the overall anti-corrosion performance.

[0037] Preferably, the aluminum castings for the motor are selected from A356 aluminum castings or ADC12 aluminum castings containing a high silicon phase.

[0038] By adopting the above technical solution, the treatment object is clearly mapped to the high-silicon aluminum alloy type commonly used in die casting or gravity casting, which meets the engineering manufacturing requirements of new energy motors and industrial motor housings for resistance to salt spray and corrosion.

[0039] This invention provides a micro-arc oxidation process for the surface of corrosion-resistant aluminum castings for motors. It offers the following advantages:

[0040] 1. This invention introduces polyaspartic acid as an adsorption shielding agent into the electrolyte and, in conjunction with parameter control during the high-frequency and low-temperature stages, enables the adsorption shielding agent to preferentially adhere to the silicon phase-rich region on the surface of the aluminum casting to form a physical insulating layer. This increases the interfacial impedance of the local micro-regions, guides the discharge current to the unshielded aluminum substrate region, improves the local discharge concentration phenomenon caused by uneven distribution of high silicon phase, and helps to obtain an initial oxide film layer with relatively uniform thickness and structure.

[0041] 2. This invention incorporates a low-frequency heating stage, utilizing the increased temperature to promote the desorption of the shielding agent, while simultaneously reducing the pulse frequency and increasing the total current density to enhance the single-pulse discharge energy. Under these operating conditions, the high-temperature sealing agent in the electrolyte is driven by the electric field into the discharge micropore channels and undergoes melting and sintering under localized high temperatures to generate a composite ceramic phase deposit. This directly fills the micropores and cooling shrinkage cracks, completing the in-situ sealing of the pores inside the oxide film, reducing the film porosity and improving the overall corrosion resistance.

[0042] 3. This invention employs a control strategy that links and adjusts temperature, flow field state, and pulse electrical parameters. In the initial stage of treatment, laminar flow is maintained to protect the integrity of the adsorption layer. In the later stage, the flow is switched to a strong turbulent state and the cathode duty cycle is increased, which accelerates the transfer of reactants in the micropores and the detachment of discharge bubbles, while reducing charge accumulation and concentration polarization on the oxide film surface. This multi-parameter collaborative control mechanism avoids sintering damage to the bottom of the pores due to local overheating, reduces the risk of powdering and loosening of the film surface, and improves the stability of film quality during long-term continuous treatment. Attached Figure Description

[0043] Figure 1 This is a graph showing the variation of voltage fluctuation variance over time within stage one of the present invention.

[0044] Figure 2 This is a graph showing the change in the occurrence rate of abnormal high current pulses over time during stage two of the present invention.

[0045] Figure 3 This is a local emission spectrum of the plasma micro-region during the second stage of this invention;

[0046] Figure 4 This is the X-ray diffraction pattern of the oxide film layer of the present invention;

[0047] Figure 5 This is a comparative diagram showing the pore resistance and porosity of the film layers in the embodiments and comparative examples of the present invention.

[0048] Figure 6The diagram shows the potential dynamic polarization curves of the oxide film layer of the present invention; wherein, (a) is a comparison diagram of the polarization curves of Examples 1 to 4 and the baseline control group Comparative Example 1, and (b) is a comparison diagram of the polarization curves of Comparative Examples 1 to 6 under different single process variables.

[0049] Figure 7 This is a comparison chart of the neutral salt spray tolerance performance of the present invention. Detailed Implementation

[0050] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0051] Preparation Examples 1-3:

[0052] Preparation Example 1:

[0053] This preparation example provides a variable impedance composite electrolyte for micro-arc oxidation treatment of corrosion-resistant aluminum castings for motors, comprising the following steps:

[0054] (1) Prepare the reference solvent: inject 100L of industrial deionized water into the mixing tank equipped with a mechanical stirring device. The conductivity of the deionized water at room temperature is 10μS / cm.

[0055] (2) Add film-forming base salt and pH adjuster: Turn on the stirrer and set the speed to 150 rpm. Slowly add 1.2 kg of industrial grade sodium silicate (Na2SiO3, equivalent to a concentration of 12.0 g / L) and 0.35 kg of potassium hydroxide (KOH, equivalent to a concentration of 3.5 g / L) to the tank in sequence, and stir for 15 min until dissolved. At this time, the pH value of the system is measured to be 12.7.

[0056] (3) Add adsorption shielding agent and high temperature sealing agent: While stirring, add 0.78 kg of industrial grade polyaspartic acid aqueous solution (PASP with a purity of 45%, equivalent to an absolute solid content of 0.35 kg and an absolute solid content concentration of 3.5 g / L) to the above alkaline silicate solution, and continue stirring for 10 min to make it uniformly dispersed; then add 0.55 kg of high temperature sealing agent (sodium tungstate) (Na2WO4·2H2O, equivalent to a concentration of 5.5 g / L), and continue stirring for 20 min until the system presents a homogeneous and transparent state, thus obtaining the variable impedance composite electrolyte.

[0057] Preparation Example 2:

[0058] This preparation example provides a variable impedance composite electrolyte for micro-arc oxidation treatment of corrosion-resistant aluminum castings for motors, comprising the following steps:

[0059] (1) Prepare the reference solvent: 100L of industrial deionized water was injected into the solution tank, and the conductivity at room temperature was measured to be 12μS / cm.

[0060] (2) Add film-forming base salt and pH adjuster: Turn on the stirrer and slowly add 0.8 kg of industrial grade sodium silicate (Na2SiO3, equivalent to a concentration of 8.0 g / L) and 0.2 kg of potassium hydroxide (KOH, equivalent to a concentration of 2.0 g / L) to the tank in sequence. Stir for 15 min until dissolved. At this time, the pH value of the system is measured to be 12.5.

[0061] (3) Add adsorption shielding agent and high temperature sealing agent: While stirring, add 0.2 kg of industrial grade polyaspartic acid (PASP, equivalent to an absolute solid content concentration of 2.0 g / L) to the above alkaline silicate solution and continue stirring for 10 min; then add 0.3 kg of high temperature sealing agent (sodium tungstate) (Na2WO4·2H2O, equivalent to a concentration of 3.0 g / L) and continue stirring for 20 min until the system dissolves to form a homogeneous solution, thus obtaining a variable impedance composite electrolyte with a concentration within the protection range.

[0062] Preparation Example 3:

[0063] This preparation example provides a variable impedance composite electrolyte for micro-arc oxidation treatment of corrosion-resistant aluminum castings for motors, comprising the following steps:

[0064] (1) Prepare the reference solvent: 100L of industrial deionized water was injected into the solution tank, and the conductivity at room temperature was measured to be 14μS / cm.

[0065] (2) Add film-forming base salt and pH adjuster: Turn on strong mechanical stirring, and slowly add 1.5 kg of industrial grade sodium silicate (Na2SiO3, equivalent to a concentration of 15.0 g / L) and 0.5 kg of potassium hydroxide (KOH, equivalent to a concentration of 5.0 g / L) to the tank in sequence, and stir for 20 min until dissolved. At this time, the pH value of the system is measured to be 12.9.

[0066] (3) Add adsorption shielding agent and high temperature sealing agent: Keep stirring and add 0.5 kg of industrial grade polyaspartic acid (PASP, equivalent to 5.0 g / L of absolute solid content) to the solution and continue stirring for 15 min; then add 0.8 kg of high temperature sealing agent (sodium tungstate) (Na2WO4·2H2O, equivalent to 8.0 g / L of concentration) and continue stirring for 30 min to ensure that the high concentration of salt dissolves to form a homogeneous system, thus obtaining a variable impedance composite electrolyte with a concentration within the protection range.

[0067] Examples 1-4:

[0068] Example 1:

[0069] This embodiment provides a micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors, including the following steps:

[0070] (1) Pretreatment: The machined ADC12 high silicon aluminum casting was immersed in a neutral degreasing solution at 50°C and ultrasonic cleaning was applied at a frequency of 35kHz for 7 minutes. After removal, it was rinsed twice in countercurrent pure water with a conductivity of less than 15μS / cm, with a single rinsing time of 2.5 minutes.

[0071] (2) Preparation of variable impedance electrolyte: The variable impedance composite electrolyte obtained in Preparation Example 1 was placed in a micro-arc oxidation tank. The pretreated aluminum casting was used as the anode and connected to a bipolar pulse power supply with PLC control, and the stainless steel tank was used as the cathode.

[0072] (3) Stage 1: High-frequency low-temperature induced shielding period treatment. Turn on the cooling function of the heat exchange coil in the tank to force the temperature of the tank liquid to 12℃; set the circulating pump to low-frequency operation to maintain the flow field of the tank liquid in a laminar state (Reynolds number Re < 2000); turn on the power supply and set the total current density to 2.0A / dm. 2 The anode duty cycle was set to 60%, the cathode duty cycle to 8%, and the bipolar pulse frequency to 1800Hz. The process was continued for 12 minutes under these conditions.

[0073] (4) Stage Two: Low-frequency heating and in-situ melting sealing treatment. After the completion of Stage One, seamless switching is performed, the cooling function of the coil is turned off, and the bath liquid is heated in a controlled manner at a rate of 1.0℃ / min using Joule heating; when the bath liquid temperature exceeds 25℃, the circulation pump is turned on at full load to switch the bath liquid to a strong turbulent state (Reynolds number Re>4000); at the same time, the total current density is stepped up to 5.0A / dm. 2 The anode duty cycle is reduced to 30%, while the cathode duty cycle is abruptly increased to 30%. As the bath temperature continues to rise, the pulse frequency is continuously and in reverse adjusted via the PLC system until the bath temperature reaches the final temperature of 40℃. At this point, the pulse frequency drops to the target low frequency of 300Hz. The total processing time for this stage is 28 minutes (i.e., 12℃ + 1.0℃ / min × 28min = 40℃).

[0074] (5) Post-processing: Disconnect the power supply and remove the workpiece. After immersing in deionized water at room temperature for 4 minutes, immerse the workpiece in deionized water at 85°C for 12 minutes for hot water sealing treatment, and finally dry it with compressed air.

[0075] Example 2:

[0076] This embodiment provides a micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors, including the following steps:

[0077] (1) Pretreatment: Immerse the A356 high silicon aluminum casting in a neutral degreasing solution at a temperature of 45℃ and apply ultrasonic cleaning at a frequency of 28kHz for 5 minutes; after taking it out, rinse it twice with deionized water in a countercurrent manner, with each rinse lasting 2 minutes.

[0078] (2) Preparation of variable impedance electrolyte: The variable impedance composite electrolyte obtained in Preparation Example 2 was placed in a micro-arc oxidation tank. The aluminum casting was connected to the anode of the power supply.

[0079] (3) Stage 1: High-frequency low-temperature induced shielding period treatment. Turn on the cooling function to control the tank liquid temperature at 10℃; maintain the circulation pump to keep the flow field in a laminar flow state; turn on the power supply and set the total current density to 1.5A / dm. 2 The anode duty cycle was set to 55%, the cathode duty cycle to 5%, and the bipolar pulse frequency was set to 1500Hz. The process was continued for 10 minutes under these conditions.

[0080] (4) Stage Two: Low-frequency heating and in-situ melting sealing treatment. Turn off the cooling function and heat the bath solution at a rate of 1.25℃ / min; when the temperature exceeds 25℃, turn on the circulation pump to switch the bath solution to a strong turbulent state; at the same time, increase the total current density to 4.0A / dm³. 2 The anode duty cycle is reduced to 25%, while the cathode duty cycle is abruptly increased to 25%. As the bath temperature rises, the pulse frequency is reversed via PLC until the bath temperature reaches 35℃, at which point the pulse frequency drops to 200Hz. The total processing time for this stage is 20 minutes (i.e., 10℃ + 1.25℃ / min × 20min = 35℃).

[0081] (5) Post-processing: Disconnect the power supply and remove the workpiece. After immersing in room temperature deionized water for 3 minutes, immerse the workpiece in deionized water at 80℃ for 10 minutes for hot water sealing treatment, and finally centrifuge to dry.

[0082] Example 3:

[0083] This embodiment provides a micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors, including the following steps:

[0084] (1) Pretreatment: Immerse the ADC12 high silicon aluminum casting in a neutral degreasing solution at 55℃ and apply ultrasonic cleaning at 40kHz for 10min; after taking it out, rinse it twice with deionized water in a countercurrent manner, with each rinse lasting 3min.

[0085] (2) Preparation of variable impedance electrolyte: The variable impedance composite electrolyte obtained in Preparation Example 3 was placed in a micro-arc oxidation tank. The aluminum casting was connected to the anode of the power supply.

[0086] (3) Stage 1: High-frequency low-temperature induced shielding period treatment. Turn on the cooling function to control the tank liquid temperature at 15℃; maintain the circulation pump to keep the flow field in a laminar flow state; turn on the power supply and set the total current density to 2.5A / dm. 2 The anode duty cycle was set to 65%, the cathode duty cycle to 10%, and the bipolar pulse frequency to 2000Hz. The process was continued for 15 minutes under these conditions.

[0087] (4) Stage Two: Low-frequency heating in-situ melting and sealing treatment. Turn off the cooling function and heat the bath solution at a rate of 0.9℃ / min; when the temperature exceeds 25℃, turn on the circulation pump to switch the bath solution to a strong turbulent state; at the same time, increase the total current density to 6.0A / dm³. 2 The anode duty cycle is reduced to 35%, while the cathode duty cycle is increased to 35%. As the bath temperature rises, the pulse frequency is reversed and reduced via PLC until the bath temperature reaches 42℃, at which point the pulse frequency drops to 400Hz. The total processing time for this stage is 30 minutes (i.e., 15℃ + 0.9℃ / min × 30min = 42℃).

[0088] (5) Post-processing: Disconnect the power supply and remove the workpiece. After immersing in deionized water at room temperature for 5 minutes, immerse the workpiece in deionized water at 90°C for 15 minutes for hot water sealing treatment, and finally blow dry with compressed air.

[0089] Example 4:

[0090] This embodiment provides a micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors, including the following steps:

[0091] (1) Pretreatment: The machined A356 high silicon aluminum casting was immersed in a neutral degreasing solution at 50°C and ultrasonic cleaning was applied at a frequency of 35kHz for 7 minutes. After removal, it was rinsed twice in countercurrent pure water with a conductivity of less than 15μS / cm, with a single rinsing time of 2.5 minutes.

[0092] (2) Preparation of variable impedance electrolyte: 100L of room temperature deionized water was injected into a mixing tank equipped with a mechanical stirrer. 1.4kg of industrial-grade potassium silicate (K2SiO3, equivalent to a concentration of 14.0g / L) and 0.2kg of potassium hydroxide (KOH, equivalent to a concentration of 2.0g / L) were added sequentially, and the pH of the system was measured to be 12.5. Subsequently, 0.35kg of industrial-grade polyaspartic acid powder (PASP, equivalent to a concentration of 3.5g / L) was added and stirred for 15min. Finally, 0.65kg of potassium tungstate (K2WO4, equivalent to a concentration of 6.5g / L) was added and stirred until dissolved to form a homogeneous electrolyte. The A356 aluminum casting was used as the anode and connected to a bipolar pulse power supply with PLC control.

[0093] (3) Stage 1: High-frequency low-temperature induced shielding period treatment. Turn on the coil cooling to force the tank liquid temperature to be controlled at 12℃; maintain the circulation pump to keep the flow field in a laminar flow state; turn on the power supply and set the total current density to 2.0A / dm. 2 The anode duty cycle was set to 60%, the cathode duty cycle to 8%, and the bipolar pulse frequency to 1800Hz. The process was continued for 12 minutes under these conditions.

[0094] (4) Stage Two: Low-frequency heating and in-situ melting sealing treatment. Turn off the coil cooling and use Joule heating to control the temperature of the bath liquid at a rate of 1.0℃ / min; when the temperature exceeds 25℃, turn on the circulation pump to switch the bath liquid to a strong turbulent state; at the same time, step up the total current density to 5.0A / dm³. 2 The anode duty cycle is reduced to 30%, while the cathode duty cycle is abruptly increased to 30%. As the bath temperature rises, the pulse frequency is continuously and in reverse adjusted via the PLC system until the bath temperature reaches the final temperature of 40°C, at which point the pulse frequency drops to the target low frequency of 300Hz. The total processing time for this stage is 28 minutes.

[0095] (5) Post-processing: Disconnect the power supply and remove the workpiece. After immersing in deionized water at room temperature for 4 minutes, immerse the workpiece in deionized water at 85°C for 12 minutes for hot water sealing treatment, and finally dry it with compressed air.

[0096] Comparative Examples 1-6:

[0097] Comparative Example 1:

[0098] Compared with Example 1, this comparative example serves as a comprehensive control group for conventional micro-arc oxidation. The differences are: no adsorption shielding agent (polyaspartic acid PASP) and high-temperature sealing agent (sodium tungstate) are added to the variable impedance composite electrolyte; the cooling function is turned on throughout the oxidation process to maintain a constant temperature of 12°C; the pulse frequency is kept constant at 1800Hz throughout the process; the cathode duty cycle is kept constant at 8% throughout the process; and all other aspects are the same.

[0099] Comparative Example 2:

[0100] The difference from Example 1 is that no adsorption shielding agent (polyaspartic acid PASP) is added to the variable impedance composite electrolyte, while all other aspects are the same.

[0101] Comparative Example 3:

[0102] Compared with Example 1, the difference is that no high-temperature sealing agent (sodium tungstate) is added to the variable impedance composite electrolyte, while all other aspects are the same.

[0103] Comparative Example 4:

[0104] Compared with Example 1, the difference is that the pulse frequency in Stage 2 is not adjusted downwards in the opposite direction, but is maintained at a high frequency of 1800Hz throughout the process, while the rest are the same.

[0105] Comparative Example 5:

[0106] Compared with Example 1, the difference is that the cathode duty cycle in Stage 2 does not increase abruptly, but is maintained at 8% throughout, while the rest are the same.

[0107] Comparative Example 6:

[0108] Compared with Example 1, the difference is that in Stage 1, laminar flow is not maintained, but the circulation pump is turned on at full load throughout the process, so that the tank liquid is always in a strong turbulent state (Reynolds number Re>4000), and the rest are the same.

[0109] Test Examples 1-6:

[0110] Test Example 1: In-situ Electrical Behavior Monitoring of Oxidation Process

[0111] The aluminum castings of motors to be treated in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 5 were selected as experimental objects, and each sample was sequentially introduced into a micro-arc oxidation tank for oxidation treatment.

[0112] A high-frequency digital oscilloscope and a non-contact Hall current probe were connected in parallel at the output of the micro-arc oxidation pulse power supply. The sampling rate of the high-frequency digital oscilloscope was set to 100 MS / s, and the trigger mode was adjusted to edge trigger to capture the transient signal of the pulse square wave.

[0113] Turn on the micro-arc oxidation equipment and continuously collect data during the total 40-minute processing cycle. Record the real-time waveform data of the forward working voltage and discharge current through the data acquisition card on the equipment.

[0114] Export the acquired raw electrical signals. For stage one, with a processing time of 0 to 12 minutes, extract the average voltage value when the arc reaches steady state and the voltage jitter variance reflecting the stability of the arc. For stage two, with a processing time of 12 to 40 minutes, extract the average peak current of single pulses during the steady-state discharge stage and calculate the occurrence rate of abnormal large pulses with peak currents exceeding 2.5 times the average value.

[0115] Table 1. Data on in-situ electrical behavior characteristics of the oxidation process

[0116] Example 1 412.6 15.34 24.78 0.83 Comparative Example 1 378.4 87.21 31.25 14.36 Comparative Example 2 345.9 142.68 45.82 28.71 Comparative Example 5 409.8 18.52 68.39 35.12

[0117] Figure 1 This is a graph showing the variation of voltage fluctuation variance over time in stage one of the present invention. The graph includes a comparison of data from Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 5. Figure 2 This is a graph showing the change in the occurrence rate of abnormal high current pulses over time during stage two of this invention. The graph includes a comparison of data from Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 5.

[0118] According to the data in Table 1, high-silicon aluminum castings exhibit localized electrical imbalances in conventional micro-arc oxidation systems. Considering the physical characteristics of the initial stage of the micro-arc oxidation reaction, the test results of Comparative Examples 1 and 2 in Stage 1 show that the arc initiation voltage is at a low level, and the voltage fluctuation variance is relatively large. In conventional systems, the insulation impedance of the high-silicon phase region is lower than that of the aluminum matrix, and the discharge channel tends to concentrate in the silicon-rich micro-region, making large arc breakdown more likely. The arc initiation voltage of Example 1 was 412.6V, and the voltage fluctuation variance was 15.34V. 2 Polyaspartic acid can preferentially adsorb or accumulate on the surface of a high-silicon phase in a laminar flow field. Through steric hindrance, it enhances the polarization impedance of the exposed silicon microregion, making the distribution of the discharge electric field at the interface between the aluminum and silicon phases nearly uniform, and maintaining a stable arc initiation process.

[0119] Further analysis of the interaction between electrical parameters and thermodynamic conditions was conducted on the test data from Phase 2. The combination of low-frequency pulses and bath temperature increases the energy input of a single pulse. Under this specific energy accumulation background, Comparative Example 5, due to the lack of a large cathode duty cycle, achieved an average single-pulse peak current of 68.39 A and an abnormal large pulse occurrence rate of 35.12%. The space charge accumulated at the micro-arc interface is difficult to dissipate in the absence of reverse voltage depolarization, often maintaining a relatively long arc duration. In Example 1, the cathode duty cycle was increased to 30% during the temperature rise and low-frequency stages, maintaining an average single-pulse peak current of 24.78 A and an abnormal large pulse occurrence rate of 0.83%. The reverse polarization process interrupted the continuous arc, maintaining the discrete state of the discharge channel. Tungstate ions, driven by the electric field in this environment, enter the membrane pores and participate in subsequent reduction and melting sealing reactions.

[0120] Test Example 2: Spectroscopic Analysis of Plasma Micro-region Discharge Characteristics During Film Formation

[0121] The aluminum castings of motors to be processed in Example 1, Comparative Example 3, and Comparative Example 4 were selected as experimental subjects and were respectively connected to a micro-arc oxidation device for processing.

[0122] A multi-channel emission spectrometer equipped with a fiber optic probe was mounted on the outside of the observation window of the tank. The probe was positioned directly against the dense micro-arc discharge area on the anode surface of the aluminum casting, and the optical focal length was adjusted to receive the plasma emission signal.

[0123] The micro-arc oxidation program was started, and spectral signals were acquired in single cycles at 10 minutes and 25 minutes of the process. The integration time of the spectrometer was set to 500 ms, and 10 consecutive acquisitions were performed, with the average spectral data taken to reduce background noise interference.

[0124] The acquired raw emission spectrum data were exported, and characteristic emission lines of elements were extracted in the wavelength range of 390 nm to 405 nm. The emission line of aluminum atoms at a wavelength of 396.1 nm was used as the matrix reference signal, and the characteristic emission line of tungsten species at a wavelength of 400.8 nm was used as the target analysis signal. The absolute peak intensities of each stage were recorded, and the ratio of the peak intensities of tungsten ions to aluminum atoms in stage two was calculated.

[0125] Table 2 Characteristic Spectral Parameters of Plasma Micro-Discharge in the Oxidation Process

[0126] Example 1 4215 312 6842 5318 0.777 Comparative Example 3 4189 15 7105 28 0.004 Comparative Example 4 4302 345 6511 1421 0.218

[0127] Figure 3 This is a local emission spectrum of the plasma micro-region in the second stage of this invention. The figure includes a comparison of the spectral signals of Example 1, Comparative Example 3 and Comparative Example 4 in the wavelength range of 390nm to 405nm.

[0128] According to the data in Table 2, no high-temperature sealing agent was added to the electrolyte of Comparative Example 3. The intensity of the tungsten ion spectral line at a wavelength of 400.8 nm was within the background noise range of the instrument, indicating that the detected tungsten luminescence signal was free from environmental influences. Comparative Example 4 contained tungstate, and maintained a fixed high-frequency pulse output during stage two. Tests showed that the peak intensity ratio of tungsten to aluminum in this sample was 0.218. The high-frequency pulse shortened the conduction time of a single positive pulse, limiting the deep electrophoretic migration of tungstate ions into the film layer, resulting in a lower number of tungsten ions participating in the plasma reaction.

[0129] In contrast, Example 1, employing a reversed pulse frequency reduction and initiating strong turbulence in the bath solution during stage two, achieved a tungsten species characteristic peak intensity of 5318 and a W species to aluminum peak intensity ratio of 0.777. The extended low-frequency pulse period provided a longer electric field driving time for the inorganic anions, and the strong turbulence compressed the thickness of the solid-liquid interface mass transfer boundary layer. Liquid-phase tungstate ions entered the micropores within the film layer, providing a basis for in-situ plasma eutectic melting and the formation of a glassy solid solution.

[0130] Test Example 3: Full-spectrum phase analysis of oxide film

[0131] The aluminum castings of motors to be treated in Example 1, Comparative Example 3, and Comparative Example 5 were selected as experimental subjects. After micro-arc oxidation treatment, each sample was ultrasonically cleaned with deionized water and dried, and then cut into square test blocks with a side length of 15 mm along the test surface.

[0132] The test block was fixed at the center of the X-ray diffractometer. The experiment used grazing incidence diffraction mode, and the fixed X-ray grazing incidence angle was set to 1.5°.

[0133] The operating voltage of the copper target radiation source was set to 40kV, and the operating current to 40mA. The detector's scanning range was set to a diffraction angle of 20° to 80°, the scanning step size was set to 0.02°, and the dwell time per step was set to 0.5s, for continuous scanning data acquisition.

[0134] Export the raw spectral data for each sample. Use phase analysis software to perform baseline smoothing and background subtraction on the data, extracting the integral area of ​​the amorphous diffuse scattering packet within the 20° to 35° range. Perform peak fitting on the main crystalline phases to obtain the absolute area of ​​each characteristic diffraction peak and the relative intensity information of the matrix.

[0135] Table 3. X-ray diffraction phase characteristic data of oxide film.

[0136] Example 1 15.2 5421 3854 1245 18450 Comparative Example 3 42.8 6102 4512 0 3120 Comparative Example 5 28.5 4895 3105 3450 6840

[0137] Figure 4 This is an X-ray diffraction pattern of the oxide film layer of the present invention. The pattern includes a comparison of the whole rock phase test data of Example 1, Comparative Example 3 and Comparative Example 5 in the range of diffraction angles from 20° to 80° by vertical translation.

[0138] According to the data in Table 3, the spectral information obtained under grazing incidence diffraction mode indicates that the test block of Comparative Example 3, due to the absence of a high-temperature sealing agent, mainly consists of gamma alumina and alpha alumina. The amorphous diffuse scattering envelope area of ​​this sample in the 20° to 35° range is 3120, and the relative intensity of the diffraction peaks on the aluminum substrate reaches 42.8%. The substrate signal indirectly reflects the presence of micropores or cracks within the conventional micro-arc oxide film, where X-rays penetrate, limiting the film's density.

[0139] The remaining two sets of data, using tungsten sources, demonstrate the control of electrical parameters on the phase transition process. Comparative Example 5, lacking a high-proportion cathode duty cycle intervention in stage two, exhibits characteristic peaks of the tungsten oxide crystalline phase in its spectrum, with an amorphous diffuse scattering area of ​​6840. This indicates that the tungsten material underwent sintering deposition in a high-temperature environment, without forming a large-scale molten glassy state. In Example 1, the integrated area of ​​the amorphous diffuse scattering area increased to 18450, the relative intensity of the aluminum substrate diffraction signal decreased to 15.2%, and a small number of tungsten characteristic peak signals were present in the spectrum. This is mainly because, in a low-frequency pulse and strong cathode polarization environment, tungstate ions entering the film layer may have participated in electrochemical conversion and plasma high-temperature eutectic reaction, forming an amorphous sealing phase containing tungsten, silicon, aluminum, and oxygen together with silicon-aluminum oxides. The formation of the glassy material filled the internal pores of the film layer, reducing the diffraction effect of the substrate and confirming the feasibility of the in-situ sealing mechanism in structural evolution.

[0140] Test Example 4: Determination of Macroscopic Film Defects and Porosity

[0141] The aluminum castings of motors to be treated in Examples 1 to 4 and Comparative Examples 1 to 6 were selected as experimental subjects. Each sample that underwent micro-arc oxidation treatment was cleaned with anhydrous ethanol and dried with cold air.

[0142] The film thickness was measured at 10 randomly selected test points on the surface of each sample using an eddy current thickness gauge, and the average value was calculated. Surface roughness parameters were measured using a stylus-type surface roughness gauge with a sampling length of 2.5 mm.

[0143] AC impedance spectroscopy was performed using a standard three-electrode system on an electrochemical workstation. A saturated calomel electrode was used as the reference electrode, and a platinum sheet was used as the auxiliary electrode. The exposed area after encapsulation with insulating tape was 1 cm². 2 The sample surface was used as the working electrode. The test medium was a 3.5% (w / w) neutral sodium chloride aqueous solution.

[0144] The sample was immersed in the solution until the open-circuit potential stabilized. A sinusoidal AC voltage excitation signal with an amplitude of 10 mV was applied, and the scanning frequency range was set from 100 kHz to 0.01 Hz. The raw data of impedance modulus as a function of frequency were derived. The pore resistance of the film was obtained by fitting the data using an equivalent circuit model, and the relative porosity index was calculated.

[0145] Table 4 Macroscopic physical characteristics and electrochemical impedance parameters of oxide film layer

[0146] Example 1 45.2 1.15 85.6 0.8 Example 2 44.8 1.21 82.4 0.9 Example 3 46.1 1.1 88.1 0.7 Example 4 43.5 1.32 76.5 1.2 Comparative Example 1 38.6 4.52 1.2 25.4 Comparative Example 2 39.4 4.1 2.5 22.1 Comparative Example 3 41.5 2.34 8.5 12.6 Comparative Example 4 42.2 1.95 15.4 8.5 Comparative Example 5 40.8 2.85 6.8 15.3 Comparative Example 6 39.1 3.85 3.1 18.7

[0147] Figure 5 This is a comprehensive comparison chart of the pore resistance and porosity of the membrane layers in the embodiments and comparative examples of the present invention. The chart shows the differences in membrane density and impermeability of Examples 1 to 4 and Comparative Examples 1 to 6 in the form of a double Y-axis.

[0148] According to the data in Table 4, the average membrane thickness of Examples 1 to 4 remained above 43 μm, the surface roughness was below 1.4 μm, and the relative porosity index was below 1.2%. The data indicate that the system without the introduction of adsorption shielding agents and inorganic sealing processes achieved a dense membrane structure in parallel tests. The comparative groups lacking specific reaction steps or additives showed a decrease in surface morphology and impermeability.

[0149] Conversely, Comparative Examples 1 and 2 did not use an adsorption shielding agent. In the initial stage of the micro-arc reaction, arc breakdown and energy concentration preferentially occurred in the high-silica phase region, resulting in ablation micropores and through-cracks on the aluminum casting surface. The surface roughness of these two sets of samples reached 4.52 μm and 4.10 μm, respectively, with relative porosity indices exceeding 20%, allowing corrosive media to easily penetrate the film and enter the substrate, resulting in low pore resistance. In Comparative Example 6, the circulation pump was activated in the initial stage of the reaction. The fluid shear force disrupted the adsorption structure of organic molecules on the silicon phase surface, weakening the initial shielding effect and increasing the relative porosity index to 18.7%.

[0150] Taking Comparative Example 3 as an example, no high-temperature sealing agent was added to the electrolyte. The ceramic layer formed by the oxidation of the substrate retained thermal stress microcracks, and the pore resistance was 8.5 × 10⁻⁶. 5 Ω·cm 2 Comparative Examples 4 and 5 contained sealing agents, but lacked the steps of pulse frequency reduction and cathode duty cycle increase in the later stages of the reaction, respectively. Insufficient electric driving force and the degree of space charge depolarization affected the migration of liquid-phase ions into the depth of the pores, resulting in incomplete eutectic reaction and a porosity index between 8.5% and 15.3%. The Example Group combined low-frequency pulses with reverse polarization parameters, allowing tungstate to undergo in-situ melting transformation within microscopic defects, and the resulting glassy solid solution filled the interconnected channels within the film structure. The pore resistance of the films in the Example Group was all above 76.5 × 10⁻⁶. 5Ω·cm 2 The above confirms the practical effectiveness of this process in improving the density of the film layer.

[0151] Test Example 5: Electrochemical Corrosion Resistance Test (Potigration Polarization Curve)

[0152] Aluminum castings of motors from Examples 1 to 4 and Comparative Examples 1 to 6 were selected as experimental subjects. The surfaces of the samples after micro-arc oxidation treatment were cleaned, and the back and edges were insulated and encapsulated with epoxy resin, retaining a center area of ​​1 cm² for the test surface. 2 The region is used as the working electrode.

[0153] A standard three-electrode test unit was assembled on an electrochemical workstation. A saturated calomel electrode was used as the reference electrode, a platinum mesh as the auxiliary electrode, and the insulated sample as the working electrode. A 3.5% (w / w) neutral sodium chloride aqueous solution was used as the test medium.

[0154] Immerse the assembled sample in the test solution and keep it stationary for 30 minutes. Continuously monitor the open circuit potential until the fluctuation range of the open circuit potential is less than 2mV, ensuring that the electrode surface and the solution system reach a stable state.

[0155] The potentiodynamic scanning range was set to 250 mV negative to 250 mV positive relative to the open circuit potential, and the scan rate was set to 1 mV / s. The electrochemical workstation was turned on to perform continuous potential scanning, and the current response signal of the sample was recorded.

[0156] Export the raw data of the polarization curves. Use analysis software to perform linear fitting of the strongly polarized region of the polarization curves using the Tafel extrapolation method, and calculate and extract the corrosion potential, corrosion current density, and polarization resistance electrochemical parameters.

[0157] Table 5 Electrochemical Potentiotropic Polarization Parameters of Oxide Film

[0158] Example 1 -0.485 <![CDATA[2.14×10 -8 ]]> <![CDATA[1.25×10 6 ]]> Example 2 -0.512 <![CDATA[3.52×10 -8 ]]> <![CDATA[8.94×10 5 ]]> Example 3 -0.468 <![CDATA[1.87×10 -8 ]]> <![CDATA[1.51×10 6 ]]> Example 4 -0.536 <![CDATA[4.25×10 -8 ]]> <![CDATA[7.62×10 5 ]]> Comparative Example 1 -0.854 <![CDATA[5.61×10 -5 ]]> <![CDATA[4.72×10 2 ]]> Comparative Example 2 -0.821 <![CDATA[4.15×10 -5 ]]> <![CDATA[6.51×10 2 ]]> Comparative Example 3 -0.745 <![CDATA[8.52×10 -6 ]]> <![CDATA[3.21×10 3 ]]> Comparative Example 4 -0.628 <![CDATA[9.24×10 -7 ]]> <![CDATA[3.35×10 4 ]]> Comparative Example 5 -0.685 <![CDATA[1.58×10 -6 ]]> <![CDATA[1.79×10 4 ]]> Comparative Example 6 -0.792 <![CDATA[2.36×10 -5 ]]> <![CDATA[1.18×10 3 ]]>

[0159] Figure 6 These are the potential kinetic polarization curves of the oxide film layer of the present invention. Among them, Figure (a) is a comparison of the polarization curves of Examples 1 to 4 and the baseline control group, Comparative Example 1, and Figure (b) is a comparison of the polarization curves of Comparative Examples 1 to 6 under different single process variables.

[0160] According to the data in Table 5, the electrochemical polarization parameters of the oxide film on the surface of aluminum castings reflect the direct impact of process conditions on the construction of the corrosion barrier. In the test environment containing sodium chloride, the corrosion current density characterizes the rate of electrochemical dissolution of the material, and a positive shift in corrosion potential indicates an improvement in the thermodynamic stability of the system. Observing the test results of Comparative Example 1 and Comparative Example 2, the corrosion current density of the samples is around 10. -5 A / cm2 The corrosion potential was below -0.8V. In Comparative Examples 1 and 2, polyaspartic acid was not added for physical adsorption shielding during the pretreatment. During the micro-arc reaction, concentrated discharge occurred in the high-silica micro-regions of the substrate due to the lack of a polyaspartic acid shielding layer, leading to micropores and penetrating cracks within the film. Corrosive chloride ions could penetrate these micropores and cracks to reach the metal substrate interface, initiating localized electrochemical dissolution. In Comparative Example 6, the circulation pump was activated at the initial stage of the reaction, causing fluid shearing. This external physical force disrupted the stability of the adsorption shielding layer, resulting in a corrosion current density of 2.36 × 10⁻⁶. -5 A / cm 2 .

[0161] The filling and repair status of the pores within the film layer determines the level of corrosion resistance. In Comparative Example 3, no high-temperature sealing agent was added to the electrolyte, and the ceramic phase formed by the oxidation of the aluminum substrate retained microcracks after cooling and shrinkage. The corrosion current density of Comparative Example 3 was 8.52 × 10⁻⁶. -6 A / cm 2 The polarization resistance is maintained at 10. 3 Ω·cm 2 The levels were different. Comparative Examples 4 and 5 added a high-temperature sealing agent, but lacked the combination of low-frequency long pulse and high cathode polarization processes in terms of electrical parameters. Insufficient electric field driving force limited the migration of tungstate ions into deeper pores, and the plasma co-melting reaction was incomplete, thus limiting the improvement in polarization resistance. The corrosion current density obtained in Examples 1 to 4 in the same corrosive medium was all reduced to 10. -8 A / cm 2 The corrosion potential shifts to above -0.53V, and the polarization resistance approaches or reaches 10. 6 Ω·cm 2 Level. Liquid tungstate enters the microscopic defects of the film layer under the drive of a low-frequency electric field and is transformed into a dense amorphous material under the action of plasma. The internal solid filler cuts off the diffusion channels of the corrosive medium, suppresses the microscopic galvanic cell effect, and improves the corrosion protection capability of aluminum castings.

[0162] Test Example 6: Accelerated Testing of Industrial Application Indicators

[0163] Aluminum castings of motors that underwent micro-arc oxidation treatment in Examples 1 to 4 and Comparative Examples 1 to 6 were selected as experimental subjects. The sample surfaces were wiped clean with anhydrous ethanol and dried with cold air. The non-working surfaces and edges of the samples were sealed with insulating tape, leaving a bare test area of ​​50 cm². 2 .

[0164] Prepare the test solution according to the neutral salt spray test specifications. Dissolve sodium chloride in deionized water and adjust the mass fraction of the solution to 5%. Use glacial acetic acid or sodium hydroxide to fine-tune the solution, controlling its pH value between 6.5 and 7.2.

[0165] The sealed samples were placed on the sample rack inside the salt spray test chamber at an angle of 15° to 30°. The continuous operating temperature inside the salt spray test chamber was set to 35°C, and the nozzles and pressure were adjusted to maintain a salt spray deposition rate of 1.0 mL / (80 cm²). 2 •h) to 2.0mL / (80cm) 2 Within the range of ·h).

[0166] The salt spray test chamber was turned on for continuous spraying. During the test, a continuous image acquisition system was used to record the surface condition of the samples. Spraying was paused every 24 hours for manual verification. The time when the first visible corrosion point (pitting pit or white rust accumulation) appeared on the surface of each sample was recorded.

[0167] All samples were removed after 2000 hours of continuous testing, and the percentage of corrosion area on each sample surface was statistically analyzed at the 1000-hour mark. Salt deposits on the surfaces were rinsed with flowing deionized water and allowed to air dry at room temperature. The percentage of corrosion area on each sample surface was calculated using a grid statistical method.

[0168] Table 6. Results of Neutral Salt Spray Accelerated Test of Oxide Film (including statistics on node corrosion area over 1000 hours)

[0169] Example 1 1680 0 Example 2 1542 0 Example 3 1825 0 Example 4 1460 0 Comparative Example 1 120 48.5 Comparative Example 2 145 42.1 Comparative Example 3 380 15.6 Comparative Example 4 624 8.4 Comparative Example 5 412 12.3 Comparative Example 6 210 35.7

[0170] Figure 7 This is a comparison chart of the neutral salt spray tolerance performance of the present invention. The chart uses a double Y-axis to indicate the time when the first corrosion point appeared in the samples of Examples 1 to 4 and Comparative Examples 1 to 6, as well as the percentage of corrosion area after 1000h of salt spray exposure.

[0171] According to the data in Table 6, the time of the first appearance of corrosion pits corresponds to the period of time it takes for corrosive ions to penetrate the film and reach the substrate. The corrosion area percentage after 1000 hours indicates the level of lateral expansion after the initiation of local electrochemical reactions. Comparative Examples 1 and 2 showed pitting corrosion at 120 hours and 145 hours of testing, respectively, with the corrosion area percentage exceeding 40% at the end of the test. The aluminum casting substrate contains a high-silicon phase, which causes concentrated local discharge energy in the early stage of micro-arc oxidation. Without the introduction of polyaspartic acid for surface physical shielding, the generated film retains unclosed micropores and thermal stress cracks. Chloride ions in the salt spray environment penetrate along macroscopic defects, accelerating the corrosion of the aluminum substrate. In Comparative Example 6, due to the high fluid shear force setting value in the early stage of the process, the stability of the organic adsorption layer was damaged, resulting in poor anti-permeation performance, and the time of the first appearance of corrosion pits was only 210 hours.

[0172] The physical filling state of deep pores affects the long-term protective performance of the film. In Comparative Example 3, no high-temperature sealing agent was added to the reaction system, and the conventional alumina ceramic skeleton could not self-heal the discharge channels generated during growth. Comparative Example 3 had a salt spray tolerance time of 380 hours, indicating that a single ceramic film faces the risk of corrosion failure under long-term high-salt environments. Comparative Examples 4 and 5 introduced high-temperature sealing agents, but did not incorporate low-frequency long-pulse and high cathodic polarization processes in their electrical parameters. Insufficient electric field driving force limited the diffusion of sealing ions to the depths of the pores, and the plasma eutectic reaction remained on the film surface, causing pitting corrosion penetration in Comparative Examples 4 and 5 after 624 hours and 412 hours, respectively. The first appearance of corrosion points in Examples 1 to 4 all exceeded 1460 hours, and no visible corrosion points were observed during the 1000-hour continuous spraying period, with a corrosion area ratio of 0%. Liquid tungstate enters the micropores under the influence of a low-frequency alternating electric field and participates in the formation of an amorphous sealing phase containing tungsten, silicon, aluminum, and oxygen in the high-temperature region of micro-arc discharge. The in-situ generated amorphous sealing material blocks the interconnected medium diffusion channels, delays the formation of localized corrosion microcells, and thus improves the environmental corrosion resistance and durability of the aluminum casting for motors.

Claims

1. A micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors, characterized in that, Includes the following steps: Pre-treatment is performed on the aluminum castings of the motor to be processed; The pre-treated aluminum casting of the motor is placed as the anode in a variable impedance composite electrolyte and connected to a pulse power supply for micro-arc oxidation treatment. Then, high-frequency low-temperature induced shielding period treatment and low-frequency heating in-situ melting and sealing period treatment are performed sequentially. In the high-frequency low-temperature induced shielding period treatment, the bath solution is controlled to maintain a constant low temperature while a high-frequency pulse current is applied; In the low-frequency heating in-situ melting and sealing process, the bath liquid is heated in a controlled manner, while the pulse frequency is reduced and the current density is increased. The variable impedance composite electrolyte is composed of a reference solvent, a film-forming base salt, a pH adjuster, an adsorption shielding agent, and a high-temperature sealing agent. Based on the aforementioned reference solvent volume, the added concentrations are: 8.0 g / L to 15.0 g / L of film-forming base salt, 2.0 g / L to 5.0 g / L of pH adjuster, 2.0 g / L to 5.0 g / L of adsorption shielding agent (equivalent to absolute solids content), and 3.0 g / L to 8.0 g / L of high-temperature sealing agent; Corrosion-resistant aluminum castings for motors can be obtained by post-processing the micro-arc oxidation treated aluminum castings.

2. The micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors according to claim 1, characterized in that, The film-forming base salt is sodium silicate or potassium silicate; The pH adjuster is potassium hydroxide; The adsorption shielding agent is polyaspartic acid; The high-temperature sealing agent is sodium tungstate or potassium tungstate; The reference solvent is deionized water with a conductivity between 10 μS / cm and 14 μS / cm at room temperature.

3. The micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors according to claim 1, characterized in that, The preparation process of the variable impedance composite electrolyte is as follows: The film-forming base salt and the pH adjuster are added sequentially to the reference solvent and stirred until dissolved to prepare an alkaline solution with a pH value controlled between 12.5 and 12.9; Add the adsorption shielding agent to the alkaline solution and stir to disperse; The high-temperature sealing agent was then added and stirred until the system became homogeneous.

4. The micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors according to claim 1, characterized in that, The preprocessing specifically includes: The aluminum casting of the motor is immersed in a neutral degreasing solution at a temperature of 45°C to 55°C and ultrasonic-assisted cleaning at a frequency of 28kHz to 40kHz is applied for 5 to 10 minutes. Remove the degreased aluminum castings from the motor and rinse them twice with countercurrent pure water in deionized water with a conductivity of less than 15 μS / cm. Each pure water rinse takes 2 to 3 minutes.

5. The micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors according to claim 1, characterized in that, The pulse power supply is a bipolar pulse power supply; The operating parameters for the high-frequency low-temperature induced shielding period treatment are set as follows: Maintain the temperature of the bath solution between 10°C and 15°C. Maintain the flow field of the tank liquid in a laminar flow state with a Reynolds number of less than 2000; The total current density is set to 1.5 A / dm². 2 Up to 2.5A / dm 2 Set the anode duty cycle to 55% to 65%, the cathode duty cycle to 5% to 10%, and the bipolar pulse frequency to 1500Hz to 2000Hz. The process continues for 10 to 15 minutes under the specified operating parameters.

6. The micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors according to claim 5, characterized in that, The operating parameters for the initial stage of the low-frequency heating in-situ melting and sealing process are adjusted as follows: Stop refrigeration and use Joule heating to raise the temperature of the bath liquid at a rate of 0.9℃ / min to 1.25℃ / min; When the temperature of the bath liquid exceeds 25℃, turn on the circulation pump to switch the flow field of the bath liquid to a strong turbulent state with a Reynolds number greater than 4000. At the same time, the total current density was increased to 4.0 A / dm³. 2 Up to 6.0A / dm 2 The anode duty cycle will be lowered to 25% to 35%, and the cathode duty cycle will be increased to 25% to 35%.

7. The micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors according to claim 6, characterized in that, During the low-frequency heating in-situ melting and sealing process, as the bath liquid continues to heat up, the bipolar pulse frequency is continuously and in reverse adjusted down through the PLC system until the bath liquid temperature reaches the final temperature of 35°C to 42°C. At this final temperature, the bipolar pulse frequency drops to 200Hz to 400Hz.

8. The micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors according to claim 7, characterized in that, The total processing time for the low-frequency heating in-situ melting and sealing treatment is 20 to 30 minutes.

9. The micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors according to claim 1, characterized in that, The post-processing specifically includes: After immersing the aluminum casting of the motor in deionized water at room temperature for 3 to 5 minutes, immerse it in deionized water at a temperature of 80°C to 90°C for 10 to 15 minutes for hot water sealing treatment, and then take it out and blow it dry.

10. The micro-arc oxidation treatment process for the surface of corrosion-resistant aluminum castings for motors according to claim 1, characterized in that, The aluminum castings for the motor are selected from A356 aluminum castings or ADC12 aluminum castings containing a high silicon phase.